Answer:
Value of (t) = 0
Step-by-step explanation:
According to the scenario no time has passed.
t = 0
Given:
f(t)= -16t² + 32t + 5.2
When t = 0
So.
f(t)= -16t² + 32t + 5.2
f(0)= -16(0)² + 32(0) + 5.2
f(0) = 5.2 feet
Simplify. 1/2−3(1/2+1)^2
Answer:
-6.25
Step-by-step explanation:
The answer is -6.25.
Point B lies between points A and C on Line segment A C . Let x represent the length of segment AB in inches.
Answer:
5,5,15
Step-by-step explanation:
At a meeting of 3 representatives from each of 6 different companies, each person shook hands once with every person not from his or her own company. If the representatives did not shake hands with people from their own company, how many handshakes took place
Answer:
135
Step-by-step explanation:
From the given information:
The total number of handshakes can be represented by the combination of 18 combination 2, which can be mathematically expressed as:
[tex]\mathbf{^{18}C_2}[/tex] .
where;
[tex]\mathbf{^{18}C_2}[/tex] is the number of ways two people can shake themselves from a total of 28 people without much regard about the order of arrangement of the handshakes.
[tex]\mathbf{^{18}C_2 = \dfrac{18!}{2!(18-2)!}}[/tex]
[tex]\mathbf{= \dfrac{18!}{2!(16)!}}[/tex]
= 153
From these 6 companies, the possibility that there will be handshakes from within the company is [tex]\mathbf{^3 C_2}[/tex]
[tex]\mathbf{^3 C_2} = \dfrac{3!}{2!(3-2)!}[/tex]
[tex]= \mathbf{ \dfrac{3 \times 2!}{2!(1)!}}[/tex]
= 3
However, number of companies = 6
∴ the number of handshakes within companies = 3 × 6 = 18
But we are being told that :
If the representatives did not shake hands with people from their own company, how many handshakes took place
Therefore, the number of handshakes that took place in regard to the given criteria = 153 - 18
= 135
14. If EF bisects CD, CG = 5x - 1, GD = 7x - 13, EF = 6x - 4, and GF = 13, find EG.
3. EF = 6-a. and Cr -13, cihad ES
Greetings from Brasil....
As stated in the statement of the question, EF is a bisector of CD, so point G is the median point of CD, so CG = GD
5X - 1 = 7X - 13
X = 6
EF = EG + GF
6X - 4 = EG + 13 x = 6, so
6·6 - 4 = EG + 13
EG = 19(see attachment)
given that is a = 3 , b = -4 and c = -2 evaluate 3a - b / 2c + 3a - c / c - b
Answer:
5.2
Step-by-step explanation:
= 3a - b / 2c + 3a - c / c - b
= 3(3) - (-4) / 2(-2) + 3(3) / -2 -(-4)
= 9 + 4 / -4 + 9 / -2+4
= 13 / 5 / 2
= 13 / 5 * 2
= 2.6 * 2
= 5.2
Answer:
Step-by-step explanation:
[tex]\frac{3a -b}{2c}+\frac{3a-c}{c-b}=\frac{3*3-[-4]}{2*(-2)}+\frac{3*3-[-2]}{-2-[-4]}\\\\=\frac{9+4}{-4}+\frac{9+2}{-2+4}\\\\=\frac{13}{-4}+\frac{11}{2}\\\\=\frac{-13}{4}+\frac{11*2}{2*2}\\\\=\frac{-13}{4}+\frac{22}{4}\\\\=\frac{-13+22}{4}\\\\=\frac{9}{4}\\\\=2\frac{1}{4}[/tex]
36+x=12-3x
Plz help quick
Answer:
x = -6
Step-by-step explanation:
36 + x = 12 - 3x
36 + x - 36 = 12 - 3x - 36
x = -3x - 24
x + 3x = -3x - 24 + 3x
4x = -24
4x / 4 = -24 / 4
x = -6
Answer:
x = -6
Step-by-step explanation:
36 + x = 12 - 3x
We need all terms with x on the left side.
Add 3x to both sides.
36 + x + 3x = 12 - 3x + 3x
36 + 4x = 12
We need all terms that are just numbers on the right side. Subtract 36 from both sides.
36 - 36 + 4x = 12 - 36
4x = -24
We have 4x, which means 4 multiplied by x, on the left side. We want x alone. Divide both sides by 4.
x = -6
What type of graph is this?
not a regular graph
a regular graph
a bus is leaving the bus station at 5:45 p.m. and it takes 2 days 6 hours 30 minutes to reach a destination if the bus leaves on Friday what will be the day and time when it arrive it destination?
Answer:
Monday, at 12:15 AM
Step-by-step explanation:
Do this question in parts. First, add 2 days to Friday to get Sunday at 5:45 PM. Then, add 6 hours to 5:45 to get 11:45 PM. Finally, add 30 minutes to 11:45 PM. That takes you to 12:15, and since you passed midnight, Sunday is now Monday. That means the bus arrives Monday, at 12:15 AM.
need help ASP. find the inverse function of f(x)=3x-4
Answer:
f (x) = 1
substitute 1 for x
f (1) = 3 (1) - 4
= 3 - 4
= -1
Answer:
[tex]y = \frac{ x + 4}{3} [/tex]
Step-by-step explanation:
Let f(x) =y
y= 3x-4
[interchanging variables]
x=3y-4
[making y the subject]
3y=x+4
Therefore the inverse of the function is
[tex]y = \frac{x + 4}{3} [/tex]
how do you solve this problem (x+5)²
Answer:
x = -5
Step-by-step explanation:
Solve for x:
(x + 5)^2 = 0
Take the square root of both sides:
x + 5 = 0
Subtract 5 from both sides:
Answer: x = -5
please help :) Write the number shown in standard notation. 5.002 x 10 to the 7 power A. 5,002,000,000 B. 50,020,000 C. 5,002,000 D. 50,020,000,000
Answer:
Hey there!
That would be 50,020,000, and choice B would be correct.
Let me know if this helps :)
Write standard form, expanded form and word form at the top of the page write five numbers that are at least 8 digits long
Answer:
See Explanation
Step-by-step explanation:
1.
Standard Form: 2 * 10^8
The number is expanded as follows:
[tex]10^8 = 100,000,000[/tex]
So: [tex]2 * 10^8 = 2 * 100,000,000[/tex]
[tex]Expanded\ Form: 200,000,000[/tex]
Word Form: Two hundred million
2.
Standard Form: 3.5 * 10^7
The number is expanded as follows:
[tex]10^7 = 10,000,000[/tex]
So: [tex]3.5 * 10^7 = 3.5 * 10,000,000[/tex]
[tex]Expanded\ Form: 35,000,000[/tex]
Word Form: Thirty five million
3.
Standard Form: 9 * 10^9
The number is expanded as follows:
[tex]10^9 = 1000,000,000[/tex]
So: [tex]9 * 10^9 = 9 * 1000,000,000[/tex]
[tex]Expanded\ Form: 9,000,000,000[/tex]
Word Form: Nine billion
4.
Standard Form: 5.5 * 10^7
[tex]10^7 = 10,000,000[/tex]
So:
[tex]5.5 * 10^7 = 5.5 * 10,000,000[/tex]
[tex]Expanded\ Form: 55,000,000[/tex]
Word Form: Fifty five million
5.
Standard Form: 4.3 * 10^7
[tex]10^7 = 10,000,000[/tex]
So:
[tex]4.3 * 10^7 = 4.3 * 10,000,000[/tex]
[tex]Expanded\ Form: 43,000,000[/tex]
Word Form: Forty Three million
What is the solution to the equation
X/6 = 4/12
X=1
x= 2
x=4
x = 6
Answer:
x = 2
because we have the same question and i got it right its hard to explain but trust me its x = 2
The solution to the given equation is 2. Therefore, option B is the correct answer.
What is an equation?In mathematics, an equation is a formula that expresses the equality of two expressions, by connecting them with the equals sign =.
The given equation is x/6 = 4/12.
The solution of an equation is the set of all values that, when substituted for unknowns, make an equation true.
Now, x/6 = 4/12
By cross multiplication, we get
12x=24
⇒ x=2
The solution to the given equation is 2. Therefore, option B is the correct answer.
To learn more about the solution of an equation visit:
https://brainly.com/question/14506845.
#SPJ2
Which solid figure has 10 edges?
Answer:
The answer to this question is pentagonal prism or pentagonal pyramid.
What is the area of a rectangle with side lengths of 5/12 foot and
2/3 foot?
Answer:
5/18
Step-by-step explanation:
Lets write an equation:
5/12*2/3=5*2/12*3.
5*2=10,
12*3=36.
10/36=5/18
The answer is 5/18.
Hope this helps!
George said that 6 x 10 to the 3 power is 180. do your Agree of Disagree? if you disagree explain the mistake he made and the correct answer. (HELP)
Answer:
The correct answer is 6000
Step-by-step explanation:
I disagree because 10 to the 3rd power = 1000 x 6 = 6000
The mistake he made was that George multiplied all of the number so, 6 x 10 x 3 = 60 x 3 = 180.
what is the answer to "sin2x=sinx" ?
Answer:
Think of the double angle formula for
sin
2
x
Explanation:
sin
2
x
=
sin
x
2
sin
x
cos
x
=
sin
x
2
sin
x
cos
x
−
sin
x
=
0
sin
x
(
2
cos
x
−
1
)
=
0
Solution A:
sin
x
=
0
⇒
x
=
k
π
,
k
∈
Z
Solution B:
2
cos
x
=
1
⇒
cos
x
=
1
2
,
x
=
±
π
3
+
2
k
π
=
π
3
(
6
k
±
1
)
,
k
∈
Z
∴
x
=
k
π
or
x
=
π
3
(
6
k
±
1
)
,
k
∈
Z
Step-by-step explanation:
Answer:
[tex]\bold{x=\frac\pi3+2k\pi\quad \vee\quad x=\frac{5\pi}3+2k\pi\quad \vee\quad x=k\pi\ ,\quad k\in\mathbb Z}[/tex]
Step-by-step explanation:
[tex]\sin 2x=\sin x\\\\\sin2x - \sin x=0\\\\2\sin x\cos x-\sin x=0\\\\(2\cos x-1)\sin x=0\\\\2\cos x-1=0\qquad\qquad\qquad\qquad or\qquad \sin x=0\\\\2\cos x=1\quad\qquad\qquad\qquad\qquad\ or\qquad \sin x=0\\\\\cos x=\frac12\qquad\qquad\qquad\qquad\qquad or\qquad \sin x=0\\\\x=\frac\pi3+2k\pi\quad \vee\ \ x=\frac{5\pi}3+2k\pi\quad\ \ \vee\ \ x=0+k\pi\ ,\quad k\in\mathbb Z[/tex]
Simplify the following expression: a + 2c − 5b − c + a − b 2a − 6b + 2c 2a − 6b + c a − 6b + c a − 5b + 2c
Answer:
=−ab2+2ac2+2ac+2a−28b+3c
Step-by-step explanation:
a+2c−5b−c+a−b2a−6b+2c2a−6b+ca−6b+ca−5b+2c
=a+2c+−5b+−c+a+−ab2+−6b+2ac2+−6b+ac+−6b+ac+−5b+2c
Combine Like Terms:
=a+2c+−5b+−c+a+−ab2+−6b+2ac2+−6b+ac+−6b+ac+−5b+2c
=(−ab2)+(2ac2)+(ac+ac)+(a+a)+(−5b+−6b+−6b+−6b+−5b)+(2c+−c+2c)
=−ab2+2ac2+2ac+2a+−28b+3c
Answer:
=−ab2+2ac2+2ac+2a−28b+3c
Answer:
B. 2a − 6b + c
Step-by-step explanation:
Took the test :)
Please solve this, will rate 5 stars and mark as STAR!
Answer:
[tex]\boxed{5 \cdot \sqrt{2} \cdot \sqrt[6]{5} }[/tex]
Step-by-step explanation:
[tex]\sqrt[3]{250} \cdot \sqrt{\sqrt[3]{10} }[/tex]
[tex]\sqrt{\sqrt[3]{10} } \implies (10^\frac{1}{3} )^\frac{1}{2} =10^\frac{1}{6} =\sqrt[6]{10}[/tex]
[tex]\therefore \sqrt{\sqrt[3]{10} }=\sqrt[6]{10}[/tex]
[tex]\text{Solving }\sqrt[3]{250} \cdot \sqrt{\sqrt[3]{10} }[/tex]
[tex]250=2 \cdot 5^3[/tex]
[tex]\sqrt[3]{250}=\sqrt[3]{2\cdot 5^3}=5 \sqrt[3]{2}[/tex]
Once
[tex]\sqrt[6]{2} \cdot \sqrt[6]{5} = \sqrt[6]{10}[/tex]
We have
[tex]5 \sqrt[3]{2} \cdot \sqrt[6]{2} \cdot \sqrt[6]{5}[/tex]
We can proceed considering the common base of exponentials
[tex]\sqrt[3]{2} \cdot \sqrt[6]{2} = 2^{\frac{1}{3}} \cdot 2^{\frac{1}{6} } = 2^{\frac{3}{6} } = 2^{\frac{1}{2} }=\sqrt{2}[/tex]
Therefore,
[tex]5 \sqrt[3]{2} \cdot \sqrt[6]{2} \cdot \sqrt[6]{5} = 5 \cdot \sqrt{2} \cdot \sqrt[6]{5}[/tex]
Please solve. 6(3 + 8) - 4/5
G'Day mate! Here's the answer:
53 1/3
1. 6(3 + 6) - 4/5
2. 6 x 3 is 18, and 6 x 8 is 48
3. 18 plus 48 is 66
4. 66 - 4/5 = 266/5
5. 266/5 as mixed number is 53 1/5
Answer:
[tex]\Large \boxed{\frac{326}{5}}[/tex]
Step-by-step explanation:
[tex]\displaystyle 6(3 + 8) - \frac{4}{5}[/tex]
Solving brackets.
[tex]\displaystyle 6(11) - \frac{4}{5}[/tex]
[tex]\displaystyle 66 - \frac{4}{5}[/tex]
Subtract.
[tex]\displaystyle \frac{66}{1} - \frac{4}{5}[/tex]
[tex]\displaystyle \frac{66 \times 5}{1 \times 5} - \frac{4}{5}[/tex]
[tex]\displaystyle \frac{330}{5} - \frac{4}{5}[/tex]
[tex]\displaystyle \frac{330-4}{5}[/tex]
[tex]\displaystyle \frac{326}{5}[/tex]
Parvin often cleans the dishes with her mother she can clean 17 plates in 10 minutes how many plays country clean in different amounts of time
How do you solve this systems of equations problem
2r +3s=-5
6s=2r
Answer:
see explanation
Step-by-step explanation:
Given the 2 equations
2r + 3s = - 5 → (1)
6s = 2r → (2) ( divide both sides by 2 ), then
r = 3s
Substitute r = 3s into (1)
2(3s) + 3s = - 5
6s + 3s = - 5
9s = - 5 ( divide both sides by 9 )
s = - [tex]\frac{5}{9}[/tex]
Substitute this value into either of the 2 equations and evaluate for r
Substituting into r = 3s, then
r = 3 × - [tex]\frac{5}{9}[/tex] = - [tex]\frac{5}{3}[/tex]
Solution is r = - [tex]\frac{5}{3}[/tex] and s = - [tex]\frac{5}{9}[/tex]
5(7x+8y) simplified
Answer:
35x+40y
Step-by-step explanation:
1. expand the terms by multiplying 5 by what's inside the parenthesis, so multiply by 7x and 8y and add them. So you get 35x+40y
Answer:
35x +40y
Step-by-step explanation:
5(7x+8y)
Distribute
5*7x + 5*8y
35x +40y
5х + 10 = 24 + 6x – 3х
Answer:
Here, 5x + 10 = 24 + 6x - 3x
or, 5x + 10 = 24 + 3x ( 6x-3x )
or, 5x - 3x = 24 - 10
or, 2x = 14
or, x = 14/2
Hence answer is 7.
You Walked around a circle which has diameter of hundred metre how far you worked
Answer:
314.16 metres
Step-by-step explanation:
The answer to this problem is essentially just the circumference of the circle.
The circumference, or perimeter, is denoted by C = 2πr = πd, where r is the radius (and half the diameter) and d is the diameter.
Here, the diameter is 100 metres, so plug this in for d:
C = πd
C = π * 100 ≈ 314.16 metres
The answer is about 314.16 metres.
~ an aesthetics lover
There are 10 cups of coffee in each coffee pot and 12 donuts per box, how many cups of coffee and how many donuts will be available if I make two pots of coffee and 3 boxes of donuts?
Answer:
There are 20 cups of coffee in two pots of coffee and 36 donuts in 3 boxes of donuts
Step-by-step explanation:
The rule of three or is a way of solving problems of proportionality between three known values and an unknown value, establishing a relationship of proportionality between all of them. That is, what is intended with it is to find the fourth term of a proportion knowing the other three.
If the relationship between the magnitudes is direct, that is, when one magnitude increases, so does the other (or when one magnitude decreases, so does the other), the direct rule of three must be applied as follow:
a ⇒ b
c ⇒ x
So [tex]x=\frac{c*b}{a}[/tex]
In this case, the rule of three can be applied as follows:
if in 1 coffee pot there are 10 cups of coffee, in 2 pots of coffee how many cups of coffee are there?[tex]amount of cups of coffe=\frac{2coffe pots*10 cups of coffee}{1 coffe pot}[/tex]
amount of cups of coffe= 20
If there are 12 donuts in 1 box, how many donuts are there in 3 boxes?[tex]amount of donuts=\frac{3 boxes*12 donuts}{1 box}[/tex]
amount of donuts= 36
There are 20 cups of coffee in two pots of coffee and 36 donuts in 3 boxes of donuts
Write an expression to represent:
Eight more than the product of two and a number
x
xx.
Answer:
2x+8
Step-by-step explanation:
The mathematical expression will be;
⇒ 2x + 8
What is an expression?Mathematical expression is defined as the collection of the numbers variables and functions by using operations like addition, subtraction, multiplication, and division.
Given that;
The algebraic expression is,
⇒ '' Eight more than the product of two and a number x''.
Now,
Since, The algebraic expression is,
⇒ '' Eight more than the product of two and a number x''.
Hence, We get the mathematical expression as;
⇒ Product of 2 and number x = 2x
And, 8 more than 2x = 2x + 8
Thus, We get the mathematical expression as;
⇒ 2x + 8
Learn more about the mathematical expression visit:
brainly.com/question/1859113
#SPJ2
simplify (2xy)3x2 will give brainliest.
Answer:
6x³y
Step-by-step explanation:
(2xy) * 3x²
We know that 2 * 3 = 6 and x * x² = x¹ * x² = x⁽¹⁺²) = x³ so the final answer is 6x³y.
Show the following conjectures are false by finding a counterexample.
13. All prime numbers are odd.
14. If the product of two numbers is positive, then the two numbers must both be positive.
15. If the sidewalk is wet, then it has been raining.
''All prime numbers are odd."
That is incorrect because if we consider the smallest odd number, 2, is an even number. We can say that except 2, all prime numbers are odd.
14. section is wrong. For example, both numbers can be negative, so when we multiple these two, it will equals a positive value.
Find the value of y
(PlZ help me). :)
Answer:
[tex]\huge \boxed{y=\sqrt{30} }[/tex]
Step-by-step explanation:
We can use ratios to solve for the problem.
y/5 = 6/y
Cross multiply.
y × y = 5 × 6
y² = 30
Take the square root of both sides.
y = [tex]\sqrt{30}[/tex]